Analisis Ketepatan Waktu Distribusi Makanan dan Kesesuaian Diet Pasien Rawat Inap dalam Evaluasi Mutu Pelayanan Gizi Rumah Sakit X - Salisya Silvi Nur Nadhifah; Amalia Rahma (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Nutrition services are an essential component in hospital healthcare systems, directly supporting patient recovery through timely and clinically appropriate nutrition. This study aimed to analyze the timeliness of meal distribution, diet appropriateness, diet types, patient satisfaction, and factors supporting efficient nutrition service at Hospital X. A descriptive quantitative observational design was employed, involving 35 inpatients, observing meal delivery, menu accuracy, and staff performance. Results showed that the majority of diet-receiving patients were male (60%), aged 20–45 years (34.3%), with most staying 2 days (60%). Meal distribution was timely: 94.3% for breakfast, 97.1% for lunch, and 100% for afternoon snacks and dinner. The most common diets were TKTP (High Calorie High Protein, 22.9%) and DMRG (Low Salt Diet, 17.1%), and all patients received diets according to medical indications (100%). Patient satisfaction regarding meal timeliness, diet appropriateness, taste, food temperature, and staff performance was mostly satisfied to very satisfied, with minor dissatisfaction (5.7%) only during breakfast due to distribution delays. Despite limited personnel, service efficiency was achieved through clear task division, effective communication, work discipline, supporting systems, and active supervision. In conclusion, nutrition services at Hospital X are effective, efficient, timely, diet-appropriate, support patient recovery, and comply with hospital service standards. The alternative hypothesis (H1) is accepted, and the null hypothesis (H0) is rejected